2018
DOI: 10.1007/s40095-018-0275-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing conditions on the quality of briquettes produced by recycling charcoal dust

Abstract: Physical and thermal properties of briquettes produced by recycling charcoal dust under different processing conditions have been reported in this study. The main aim was to investigate the effects of the binder and processing conditions on the properties of briquettes. The effect of adding molasses binder on combustion properties of the briquette was first assessed. Then by fitting experimental data, mathematical models to predict gross calorific value, ash content, moisture content, relaxed density and shatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…The relationship between the moisture content and the mixing ratio with the quantity of the binder in the briquette was established to be significant as depicted in Table 4. The moisture content of the briquette follows an increasing trend with the quantity of binder which has also been reported for briquettes produced from recycled charcoal dust (Tanui et al 2018). However, it increased with a decrease in the JSS-EcWS mixing ratio as shown in Figure 3.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The relationship between the moisture content and the mixing ratio with the quantity of the binder in the briquette was established to be significant as depicted in Table 4. The moisture content of the briquette follows an increasing trend with the quantity of binder which has also been reported for briquettes produced from recycled charcoal dust (Tanui et al 2018). However, it increased with a decrease in the JSS-EcWS mixing ratio as shown in Figure 3.…”
Section: Resultssupporting
confidence: 76%
“…The effect of variation in the mixing proportion and quantity of the binder on the moisture content of the JSS-EcWS briquette was established; the moisture content of the briquette was found to have a mean value of 11.51% with a range of 10.54 to 12.41% at the corresponding mixing ratios of 50 : 50 and 75 : 25, while the quantity of the binder in each mixing ratio was 70 and 80 g, respectively. The optimum moisture content of the briquette was found to be 10.88% at a mixing ratio and binder quantity of 75 : 25 and 60 g. The range obtained for the moisture content of the JSS-EcWS briquette is similar to that of sawdust and wheat-straw briquettes, lignite briquettes, and charcoal dust briquettes (Wamukony and Jenkins 1995; Olugbade and Ojo 2021; Tanui et al 2018). The optimum moisture content range for the briquette raw material was reported to be 12-20%.…”
Section: Resultsmentioning
confidence: 84%
“…This can be through effectively drying the material waste to remove all moisture and allowing more oxygen during the process of heating to let the material waste turn completely to carbon from its original organic nature. It is also suggested that the smoke produced can largely be minimized by mixing various types of waste and processing them together [82,83].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, olive stones of particle size less than 0.425 mm torrefied at 300 • C for 30 min contain much less hemicellulose but more cellulose than raw biomass. High cellulose-containing biomass elevates the burning temperature and longevity of briquettes in a woodstove [117,118]. Thus, the cellulose lean (7.9 wt.…”
Section: Discussionmentioning
confidence: 99%